2015
DOI: 10.1038/ncomms7402
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for full-spectrum inhibition of translational functions on a tRNA synthetase

Abstract: The polyketide natural product borrelidin displays antibacterial, antifungal, antimalarial, anticancer, insecticidal and herbicidal activities through the selective inhibition of threonyl-tRNA synthetase (ThrRS). How borrelidin simultaneously attenuates bacterial growth and suppresses a variety of infections in plants and animals is not known. Here we show, using X-ray crystal structures and functional analyses, that a single molecule of borrelidin simultaneously occupies four distinct subsites within the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 58 publications
(70 reference statements)
3
81
0
Order By: Relevance
“…Pharmacological studies have revealed that borrelidin exhibits anti-malarial, anti-angiogenesis and antifungal activities, [33][34][35] and borrelidin is also known as a strong inhibitor of threonyl-tRNA synthetase. 36,37) Although a variety of biological activity has been reported, there are no reports related to anti-obesity effect of borrelidin.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological studies have revealed that borrelidin exhibits anti-malarial, anti-angiogenesis and antifungal activities, [33][34][35] and borrelidin is also known as a strong inhibitor of threonyl-tRNA synthetase. 36,37) Although a variety of biological activity has been reported, there are no reports related to anti-obesity effect of borrelidin.…”
Section: Resultsmentioning
confidence: 99%
“…4 So, inhibitors of AARSs have been used as medicine or rigorously tested in clinical trials for therapeutic applications in microbial infections, such as, the natural product mupirocin, an inhibitor of Isoleucyl-tRNA synthetase (IleRS), is approved as a topical treatment for bacterial skin infections. 7 Tyrosyl-tRNA synthetase (TyrRs) is one of the 20 Aminoacyl-tRNA synthetases and plays an important role in protein synthesis. 8 Nitroimidazole derivatives have exhibited broad variety biological activities, particularly antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Chloroquine and artemisinin have been critical treatments for this infection, unfortunately resistance to both drugs has arisen. 16 Borrelidin inhibits threonine-tRNA synthetase (ThrRS), preventing the amino acid activation step and halting protein synthesis 17 and is effective against malaria, including drug-resistant strains. 12,18 Unfortunately, borrelidin is not selective for the malarial ThrRS over the human homolog.…”
mentioning
confidence: 99%